Women who fall by the roadside: gender, sexual risk and alcohol in rural Uganda - Wolff, Brent; Busza, Joanna; Bufumbo, Leonard; Whitworth, Jimmy (Addiction, 2006)
To investigate community perceptions about the different relationship between alcohol consumption and sexual risk-taking for men and women in a high HIV prevalence African setting Design and setting Participatory learning and action (PLA) activities were conducted in five rural villages in south-western Uganda in 2002. For each village, discussions and visualization activities over the course of 5 days explored local concepts of fun, drinking alcohol and HIV-related behavioural risks. Twelve focus group discussions (FGDs) investigated emerging themes. Analysis is based on visual outputs, observation notes and focus group transcripts. Participants Attendance at sex-segregated PLA sessions was open to all village residents. FGDs were purposively sampled from drinkers and general population groups. Findings For men, drinking is conducted invariably outside the home, usually at night in bars, emphasizing independence, masculinity and freedom from domestic responsibilities. For women, drinking outside male supervision challenges feminine ideals of domesticity and signifies potential sexual vulnerability. Accepting drinks from men was viewed as signifying assent to sex and refusal could justify men resorting to sexual coercion. Even though drinking is seen to promote sexual risk, HIV prevention campaigns were considered unwelcome in bars. Communities preferred seminars involving drinkers and non-drinkers alike. Conclusions Public drinking in this community serves as a marker for men willing to exercise privileges of independence (sexual and otherwise) and women willing to defy gender norms (and risk the sexual consequences). The social and symbolic context of drinking suggests why effective HIV prevention around alcohol should not be limited to drinking environments alone.
Keywords: Alcohol; Gender; Sex behavior; Social norms; Uganda